Perkembangan Teknologi Pengering surya - Wibowo, Harry Setyo (Universitas Nusa Putra, 2020)
Solar dryers used in agriculture for food and crop drying are used for industrial drying processes. They can be proved to be a very useful device from the energy conservation point of view. It not only saves energy but also saves a lot of time, occupies less area, improves quality of the product, makes the process more efficient, and also protects the environment. Solar dryers circumvent some of the major disadvantages of classical drying. Solar drying under controlled conditions of temperature and moisture removing rate ensures perfect drying and desirable product quality. The percentage of moisture content in different agricultural products is different and varies product to product. For drying different moisture content products, the drying systems are usually classified as low and high temperature operated drying systems. The indirect, direct, and mixed mode dryers that have shown potential in drying agricultural products in the tropical and subtropical countries are discussed. A side from identifying the active and passive mode solar dryers, they also highlight the environmental influence on solar energy (harnessing) that plays a vital role in the solar drying sector. The classifications of sun drying procedures are created based on the stage of processing, the location of drying, or the apprehension to solar radiation. This paper also presents the related technologies that can help improve existing solar dryers.